Amblyomma sculptum Salivary PGE2 Modulates the Dendritic Cell-Rickettsia rickettsii Interactions in vitro and in vivo - Esteves, Eliane; Bizzarro, Bruna; Costa, Francisco Borges; Ramírez-Hernández, Alejandro; Peti, Ana Paula Ferranti; Cataneo, Allan Henrique Depieri; Wowk, Pryscilla Fanini; Timóteo, Rodolfo Pessato; Labruna, Marcelo Bahia; Silva Junior, Pedro Ismael; Silva, Célio Lopes; Faccioli, Lúcia Helena; et al. (Frontiers in Immunology, 2019)
Amblyomma sculptum is an important vector of Rickettsia rickettsii, causative agent of Rocky Mountain spotted fever and the most lethal tick-borne pathogen affecting humans. To feed on the vertebrate host’s blood, A. sculptum secretes a salivary mixture, which may interact with skin resident dendritic cells (DCs) and modulate their function. The present work was aimed at depicting the A. sculptum saliva-host DC network and the biochemical nature of the immunomodulatory component(s) involved in this interface. A. sculptum saliva inhibits the production of inflammatory cytokines by murine DCs stimulated with LPS. The fractionation of the low molecular weight salivary content by reversed-phase chromatography revealed active fractions eluting from 49 to 55% of the acetonitrile gradient. Previous studies suggested that this pattern of elution matches with that observed for prostaglandin E2 (PGE2) and the molecular identity of this lipid mediator was unambiguously confirmed by a new high-resolution mass spectrometry methodology. A productive infection of murine DCs by R. rickettsii was demonstrated for the first time leading to proinflammatory cytokine production that was inhibited by both A. sculptum saliva and PGE2, a result also achieved with human DCs. The adoptive transfer of murine DCs incubated with R. rickettsii followed by treatment with A. sculptum saliva or PGE2 did not change the cytokine profile associated to cellular recall responses while IgG2a-specific antibodies were decreased in the serum of these mice. Together, these findings emphasize the role of PGE2 as a universal immunomodulator of tick saliva. In addition, it contributes to new approaches to explore R. rickettsii-DC interactions both in vitro and in vivo.